OP0182 The Impact of Statin Use on Structural Bone Damage in Rheumatoid Arthritis. (9th June 2015) - Finckh, A.; Neto, D.; Lubbeke, A.; Moeller, B.; Ciurea, A.; Zufferey, P.; Gabay, C.
Abstract : Background: Statins are widely used serum cholesterol-lowering drugs. Because of the increased CV risk many rheumatoid arthritis (RA) patients are receiving statin therapy. Statins have also been linked to anti-inflammatory effects, but its effects on inflammatory activity have been inconsistent in the literature. More recently, statins have been associated with effects on bone metabolism, such as increased bone mineral density, decreased fracture risk, and lower risk of periprosthetic osteolysis following total hip arthroplasty. The impact of statins on the progression of structural joint damage in RA has not been studied. Objectives: To compare the rate of radiographic damage progression in RA patients using concomitant statins or not in a large prospective RA cohort. Methods: This is a prospective observational cohort study nested within the Swiss RA registry (SCQM-RA). The SCQM monitors disease activity, radiographic damage, patient characteristics and treatments at regular intervals. All patients in the SCQM-RA database with sequential X-rays and information on statin use were included. The exposure of interest was concomitant statin use as reported by the treating rheumatologist and/or the patient and categorized as ever or never. To minimize exposure misclassification or false negatives, we excluded patients with hypercholesterolemia, but no information on lipid lowering therapy. The primary end point was radiographic disease progression as measured by the rate of change from baseline in radiographic damage scores. The damage score (ERO) was assessed on 38 joints of hands and feet with a validated scoring method (Ratingen score) by a single experienced reader, blinded to clinical history. We analyzed the rate of ERO progression in pts treated with statins or not using a mixed regression model for longitudinal data, adjusting for potential confounding factors. Results: 4213 RA patients with a median of 4 [2-6] sequential X-rays/pt and 3.9 [2.0-6.4] years of follow-up/pt were included. 493 (11%) of pts were taking statins during follow-up. Statin users were significantly more often males (34% versus 23%, p<0.001), older (mean age 58 versus 54 years, p<0.001) and overweight (mean BMI 27.0 versus 24.9, p<0.001). RA treatment and disease characteristics were balanced between statin-users and non-users. After adjusting for differences in baseline prognostic factors, we found no significant difference in ERO progression in statin-users compared to non-users (ERO progression in statin-users 0.98% of the maximum score per year (95% CI: 0.46 – 1.49), compared to 0.95% (95% CI: 0.70 – 1.20); p=0.36). Disease characteristics associated with higher ERO were male sex, longer disease durations, rheumatoid factor positivity, higher disease activity and treatment types. Conclusions: The results of this study do not support the hypothesis that statins are protecting against progression of structural joint damage and bone erosions in RA patients. Disclosure of Interest: None declared